Dense white trichome production by plants as possible mimicry of arthropod silk or fungal hyphae that deter herbivory. (7th January 2015) - Yamazaki, Kazuo; Lev-Yadun, Simcha
Abstract: Some spiders are well-known to mimic flowers or other plant surfaces in order to be cryptic to both their prey and their predators. We propose that dense, thread-like white trichomes of some plants from Estonia, Greece, Israel and Japan visually mimic spider webs, lepidopteran and spider-mite web nests and plant-pathogenic fungi, and that it may result in reduced herbivory, since various herbivores avoid spider- or other arthropod webs to circumvent predation or toxic attacks, or refrain from colonizing plants that have already been occupied by other herbivores and pathogens. Spiders and other web-forming arthropods are also the prey of certain vertebrate predators and wasps, and therefore such predators may be attracted to these web-like plant structures and prey on the invertebrate herbivores occupying them. We do not dismiss the possibility that these web-like structures may also have other defensive or physiological functions or that they are not classic mimics but rather exploit the herbivore׳s perceptual state concerning the avoidance of potentially risky objects. Highlights: Anti-herbivory animal mimicry by plants has been rarely recognized. Several plants growing in Israel, Estonia, Greece and Japan have dense thread-like trichomes. These trichomes resemble spider webs or other arthropod silk nests. Spider webs are dangerous objects for herbivores because of the predatory habit and toxins. The trichomes may deter herbivores by visual mimicry or perceptual exploitation.